2022
DOI: 10.1002/jbt.23018
|View full text |Cite
|
Sign up to set email alerts
|

Potential thiosemicarbazone‐based enzyme inhibitors: Assessment of antiproliferative activity, metabolic enzyme inhibition properties, and molecular docking calculations

Abstract: A new series of thiosemicarbazone derivatives (1–11) were prepared from various aldehydes and isocyanates with high yields and practical methods. The structures of these compounds were elucidated by Fourier transform infrared, 1H‐nuclear magnetic resonance (NMR), 13C‐NMR spectroscopic methods and elemental analysis. Cytotoxic effects of target compounds were determined by 2,3‐bis‐(2‐methoxy‐4‐nitro‐5‐sulfophenyl)‐2H‐tetrazolium‐5‐carboxanilide assay and compound 1 showed significant cytotoxic activity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…The antiproliferation of malignant cells is mediated by molecules involved in cell cycle regulation, which suppress uncontrolled cell proliferation (Altay et al, 2019; Yakan et al, 2022). Molecular studies have shown that CuI halts the cell cycle via Aurora kinases, which play a role in the mitosis stage of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antiproliferation of malignant cells is mediated by molecules involved in cell cycle regulation, which suppress uncontrolled cell proliferation (Altay et al, 2019; Yakan et al, 2022). Molecular studies have shown that CuI halts the cell cycle via Aurora kinases, which play a role in the mitosis stage of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mTOR inhibitors have been reported to prevent tumor development by significantly reducing the proliferative activity of HCC cells and increasing the apoptotic effect (Semela et al, 2007;Sieghart et al, 2007). Preclinical studies on some of the mTOR inhibitors in HCC models are continuing (Zhu et al, 2014). Furthermore, studies have shown abnormally activated MAPK cascade in HCC with HBV infection (Diniz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] Inhibitor IC 50 values have been determined using the following studies: The activities of thiosemicarbazone derivatives were tested at various inhibitor concentrations, and graphs (Figure 1) were constructed as percent activity -[I], with IC 50 values determined from the equation of the curve. [41]…”
Section: Determination Of Anti-alzheimer's Disease Potentialmentioning
confidence: 99%
“…In this study, new thiosemicarbazones bearing Schiff-bases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) were accomplished by condensation reaction with 4-hydroxy-3, 5-dimethoxy benzaldehyde and various isocyanates under reflux in ethanol. The structures of the compounds were characterized by Fourier transform infrared (FT-IR), proton-carbon nuclear magnetic resonance ( 1 H NMR, 13 C NMR), and ultraviolet-visible (UV-Vis) spectroscopic methods and elemental analysis.…”
mentioning
confidence: 99%